Mould steels repaired by laser welding - Borrego, L. P. (2008)
Laser-deposit welding, by using Nd-YAG, is a mould repairing process, which has the advantages relatively to the traditional methods of achieving a less change of the metal composition around the repaired zone and permitting a very accurate deposition of a small volume of the filler material in the area chosen at the work-piece surface. This paper presents a fatigue study in specimens of two base materials used in mould production (AISI H13 and P20). Filler material as well as welding parameters were analysed in order to obtain better fatigue strength. The tests were carried out under constant amplitude loading, with two stress ratios R = 0 and R = 0.4. Welded specimens were prepared with V notches and filled with laser welding deposits. The fatigue results are presented in the form of S-N curves obtained in welded and non-welded conditions. Complementary measurements of hardness profiles and SEM analysis were carried out to understanding the fatigue behaviour and failure sites. The laser-deposit material was the weaker region in both steels, due to a high level of tensile residual stresses and also to some planar defects that are potential failure sites. Fatigue crack initiation is therefore reduced and the fatigue propagation life is enhanced. A significant mean stress effect in the base material was also observed in both mould steels.